Effect of histology on the efficacy of immune checkpoint inhibitors in advanced non-small cell lung cancer: A systematic review and meta-analysis - Li, Feng; Zhai, Suokai; Lv, Zhuoheng; Yuan, Ligong; Wang, Shuaibo; Jin, Donghui; Yi, Hang; Fu, Li; Mao, Yousheng (Frontiers in Oncology, 2022)
Background Little is known about the effect of histology on the efficacy of immune checkpoint inhibitors (ICI) in non-small-cell lung cancer (NSCLC). We conducted a systematic review and meta-analysis to assess the potential differences in the efficacy of ICIs between squamous NSCLC (SQ-NSCLC) and non-squamous NSCLC (non-SQ-NSCLC). Methods Systematic searches of PubMed, Embase, Scopus, and Cochrane Library databases were conducted. All randomized clinical trials of ICIs with available hazard ratios (HR) for progression-free survival (PFS) or overall survival (OS) according to histology were included. The primary endpoint was to assess the difference in the efficacy of ICIs between SQ-NSCLC and non-SQ-NSCLC, measured by the ratio of the HR in SQ-NSCLC to the HR in non-SQ-NSCLC (RHR). Results A total of 40 trials were included in the meta-analysis. ICI monotherapy could improve OS in both SQ-NSCLC (OS-HR 0.71, 95% CI 0.65-0.77) and non-SQ-NSCLC (OS-HR 0.80, 95% CI 0.73-0.87) while OS benefit was larger in SQ-NSCLC (OS-RHR 0.89, 95% CI 0.80-0.99). In terms of PFS, ICI monotherapy could reduce the risk of progression by 35% (PFS-HR 0.65, 95% CI 0.56-0.77) in SQ-NSCLC while the PFS benefit was smaller (10%) and not statistically significant in non-SQ-NSCLC (PFS-HR 0.90, 95% CI 0.76-1.07). Similarly, ICI-based combination treatments could reduce the risk of both progression and death in SQ-NSCLC (OS-HR 0.70, 95% CI 0.61-0.80; PFS-HR 0.56, 95% CI 0.48-0.65) and non-SQ-NSCLC (OS-HR 0.78, 95% CI 0.74-0.83; PFS-HR 0.63, 95% CI 0.57-0.69) while the survival benefits were larger in SQ-NSCLC (OS-RHR 0.83, 95% CI 0.70-0.99; PFS-RHR 0.82, 95% CI 0.70-0.96). Conclusions ICIs could deliver survival benefits in both SQ-NSCLC and non-SQ-NSCLC while the magnitude of survival benefits was histology-dependent. Future researches should consider the effect of histology on the efficacy of ICIs.